Debugging embedded microprocessor systems - Ball, Stuart R., 1956- (Newnes, 1998)
Debugging Embedded Microprocessor Systems provides techniques for engineers, technicians, and students who need to correct design faults in embedded systems. Using real-world scenarios, designers can learn practical, time-saving ways to avoid and repair potentially costly problems. Prevention is stressed. In this book, the author addresses hardware and software issues, including up-front design techniques to prevent bugs and contain design creep. Practical advice includes descriptions of common tools which can be used to help identify and repair bugs, as well as test routines. RTOS and embedded.